Management of Extramedullary Intradural Spinal Tumors: The Impact of Clinical Status, Intraoperative Neurophysiological Monitoring and Surgical Approach on Outcomes in a 12-Year Double-Center Experience - Cofano, Fabio; Giambra, Carlotta; Costa, Paolo; Zeppa, Pietro; Bianconi, Andrea; Mammi, Marco; Monticelli, Matteo; Di Perna, Giuseppe; Junemann, Carola Vera; Melcarne, Antonio; Massaro, Fulvio; Ducati, Alessandro; et al. (Frontiers in Neurology, 2020)
Objective: Intradural Extramedullary (IDEM) tumors are usually treated with surgical excision. The aim of this study was to investigate the impact on clinical outcomes of pre-surgical clinical conditions, intraoperative neurophysiological monitoring (IONM), surgical access to the spinal canal, histology, degree of resection and intra/postoperative complications. Methods: This is a retrospective observational study analyzing data of patients suffering from IDEM tumors who underwent surgical treatment over a 12 year period in a double-center experience. Data were extracted from a prospectively maintained database and included: sex, age at diagnosis, clinical status according to the modified McCormick Scale (Grades I-V) at admission, discharge, and follow-up, tumor histology, type of surgical access to the spinal canal (bilateral laminectomy vs. monolateral laminectomy vs. laminoplasty), degree of surgical removal, use and type of IONM, occurrence and type of intraoperative complications, use of Ultrasonic Aspirator (CUSA), radiological follow-up. Results: A total number of 249 patients was included with a mean follow-up of 48.3 months. Gross total resection was achieved in 210 patients (84.3%) mostly in Schwannomas (45.2%) and Meningiomas (40.4%). IONM was performed in 162 procedures (65%) and D-wave was recorded in 64.2% of all cervical and thoracic locations (99 patients). The linear regression diagram for McCormick grades before and after surgery (follow-up) showed a correlation between preoperative and postoperative clinical status. A statistically significant correlation was found between absence of worsening of clinical condition at follow-up and use of IONM at follow-up (p = 0.01) but not at discharge. No associations were found between the choice of surgical approach and the extent of resection (p = 0.79), the presence of recurrence or residual tumor (p = 0.14) or CSF leakage (p = 0.25). The extent of resection was not associated with the use of IONM (p = 0.91) or CUSA (p = 0.19). Conclusion: A reliable prediction of clinical improvement could be made based on pre-operative clinical status. The use of IONM resulted in better clinical outcomes at follow-up (not at discharge), but no associations were found with the extent of resection. The use of minimally invasive approaches such as monolateral laminectomy showed to be effective and not associated with worse outcomes or increased complications.